Student loans in China : efficiency, equity, and social justice - Cheng, Baoyan, 1975- (Emerging perspectives on education in China., 2011)
Providing the most updated information on the current financial aid system, especially the Government-subsidized Student Loan Program, in China, this book employs a multi-perspective approach to studying this loan program. Adopting an interdisciplinary framework, the book goes beyond examining the technical aspects of setting up a student loan program; it puts the loan program in a larger context of social stratification, equality and social justice.